IMPLEMENTING PRINCIPAL LEADERSHIP TO PARENTING PROGRAM AT EARLY CHILDHOOD EDUCATION - Arifin, Imron (Universitas Pendidikan Indonesia, 2017)
Principal leadership in building the school and family ties in the education of children in schools through a parenting program is important and Necessary to support and encourage the growth and development of children. Parenting programs in early childhood meant that children's education is not only the responsibility of the school but rather a shared responsibility. The purpose of this study is: know the principal's leadership in implementing parenting programs; forms of parenting programs implemented in early childhood education institutions. This study was designed with a qualitative approach. Data were collected through interviews, observation and documents. The results Showed that the principal's leadership played a psycho-religious educators. In managerial principal's plan, implement, establish relationships, and conduct monitoring and evaluation of the parenting program. In the application of parenting found 5 program include: the group of parent meetings; the involvement of parents in the group; Parental involvement in the event together; the consultation of parents; and home visits.